2011
DOI: 10.1007/s13238-011-1116-0
|View full text |Cite
|
Sign up to set email alerts
|

ERp44 C160S/C212S mutants regulate IP3R1 channel activity

Abstract: Previous studies have indicated that ERp44 inhibits inositol 1,4,5-trisphosphate (IP 3 )-induced Ca 2+ release (IICR) via IP 3 R 1 , but the mechanism remains largely unexplored. Using extracellular ATP to induce intracellular calcium transient as an IICR model, Ca 2+ image, pull down assay, and Western blotting experiments were carried out in the present study. We found that extracellular ATP induced calcium transient via IP 3 Rs (IICR) and the IICR were markedly decreased in ERp44 overexpressed Hela cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Dysregulation of IP 3 R can lead to pathological changes in Ca 2+ signaling, signal initiation, amplitude and frequency of Ca 2+ signals, duration of Ca 2+ elevation, and abnormal growth and apoptosis of cells . Complex regulation of Ca 2+ signaling is required for cells to live and function, and this task can only be managed when the IP 3 R properly binds with its numerous binding partners . ERp44 is an inhibitor of IP 3 R1; therefore, Ca 2+ dysregulation in ERp44‐deficient cardiac cells is likely through an IP 3 R1 Ca 2+ release pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of IP 3 R can lead to pathological changes in Ca 2+ signaling, signal initiation, amplitude and frequency of Ca 2+ signals, duration of Ca 2+ elevation, and abnormal growth and apoptosis of cells . Complex regulation of Ca 2+ signaling is required for cells to live and function, and this task can only be managed when the IP 3 R properly binds with its numerous binding partners . ERp44 is an inhibitor of IP 3 R1; therefore, Ca 2+ dysregulation in ERp44‐deficient cardiac cells is likely through an IP 3 R1 Ca 2+ release pathway.…”
Section: Discussionmentioning
confidence: 99%
“…9 Complex regulation of Ca 2+ signaling is required for cells to live and function, and this task can only be managed when the IP 3 R properly binds with its numerous binding partners. 46 ERp44 is an inhibitor of IP 3 R1 8,47 ; therefore, Ca 2+ dysregulation in ERp44-deficient cardiac cells is likely through an IP 3 R1 Ca 2+ release pathway. Our results indicated that dysfunctional ERp44-enhanced Ca 2+ release amplitude can be further amplified by stimulation with 1 mmol/L of histamine (IP 3 R agonist), which supports the idea that ERp44 inhibits IP 3 R1 in cardiomyocytes in vitro and in vivo, at least under normal cellular environments.…”
Section: Ip 3 R Ryr 2 and Ca 2+ Dynamics In Erp44-deficient Modelsmentioning
confidence: 99%
“…immunoprecipitation showed that ERP44 could directly bind to IP3R1. ERP44 directly interacts with IP3R1 and inhibits IP3-induced Ca 2+ release 13,40 . IP3-induced Ca 2+ release is decreased in HeLa cells overexpressing ERP44 through IP3R channels 40 .…”
Section: Discussionmentioning
confidence: 99%
“…ERP44 directly interacts with IP3R1 and inhibits IP3-induced Ca 2+ release 13,40 . IP3-induced Ca 2+ release is decreased in HeLa cells overexpressing ERP44 through IP3R channels 40 . The level of Ca 2+ in H/Rinduced mitochondria was decreased clearly after overexpression of ERP44, indicating that the binding of ERP44 to IP3R1 inhibited the MI/R-induced mitochondrial Ca 2+ overload.…”
Section: Discussionmentioning
confidence: 99%
“…Higo and his colleagues [ 15 ] reported that ERP44 binds to IP 3 R1, a vital Ca 2+ channel on the ER membrane, and regulates intracellular Ca 2+ concentrations by modulating IP 3 R1 activity. Our previous studies showed that IP 3 -induced Ca 2+ release is decreased in ERP44 overexpressed HeLa cells and that C160/212 of ERP44 influences the binding capacity between IP 3 R1 and ERP44 [ 16 ]. However, the role and mechanism of ERP44 in regulating cell migration are unknown.…”
Section: Introductionmentioning
confidence: 99%